Multimedia elements and internet - J. Badi, Maimona; Zeki, Akram M. (IIUM Press, 2011)

(untitled)
With the fast improvement In Internet speed and the high technology in various devices, applying multimedia elements became so easy and important in daily life use in different areas in business and general uses. However applying multimedia elements improves the human interaction with devices through internet and improves also worldwide communications anywhere anytime.